Capacity strengthening strategy through capacity needs assessment for Country Level Strategic Analysis and Knowledge Support System (SAKSS): Ghana - Dittoh, Saa (International Food Policy Research Institute, 2014)
The objective of this Capacity Needs Assessment (CNA) study is to identify where and how to improve Ghana’s agricultural policy analysis, investment planning, implementation, M&E, and knowledge management. To achieve this objective, researchers first needed to identify and understand country‐level capacities, skills, and analytical tools that already exist and function effectively in addition to ones that are deficient or nonexistent. The CNA was conducted at three levels: the policy process/enabling environment level, organizational level, and individual level. The assessment focused on the thematic issues related to (1) strategic policy analysis, (2) M&E, and (3) knowledge management and sharing. Thirteen organizations were covered in this assessment, including government ministries, research organizations, universities, and professional associations.